Preschool Teachers' Perceptions Towards the Use of Play- Based Approach in Language and Literacy Development for Preschool - Sharifah Nor Puteh; Aliza Ali (UUM Press, 2013)
Purpose - In the new mandatory National Preschool Curriculum Standards introduced by the Ministry of Education Malaysia, the play-based approach has been emphasized in the teaching and learning process. This study aimed to find out teachers' perception towards the use of the play-based approach in the language and literacy development of preschoolers.   Method - A structured questionnaire survey was the main instrument used for data collection. The respondents consisted of 60 teachers from four agencies which provide preschool education, namely the Ministry of Education, KEMAS, Jabatan Perpaduan Negara (JPN), and private preschool centers in the district of Hulu Langat Selangor. All respondents were randomly selected. Of the 60, 51 respondents completed the survey. To gain additional insights into teachers' perceptions 12 respondents were purposely selected from this group to be interviewed. One-way ANOVA was used to analyze data from the survey.   Findings - The results showed that teachers have a positive response towards a play-based approach in preschoolers' language and literacy development. They believed children like to play and are actively involved in play. However, they were unsure about the use of play based approach. Issues and constraints such as time allocation for play activities, limited and unsuitable space for play, and lack of knowledge and skills required to implement developmentally appropriate teaching including play, made them resort to a didactic teacher-directed approach in their classrooms.   Significance - The study points to the importance of providing teachers with knowledge and skills on the use of play in their teaching approach. Intervention programs and collaborations among the agencies providing preschool education must be established to enhance the quality of teaching practices and to ensure the new curriculum is effectively implemented.